CORAL POINT COUNT WITH EXCEL EXTENSIONS (CPCE) SOFTWARE: CORAL REEF CONDITION AT SMALL ISLANDS IN INDONESIA - Utami, Risnita Tri; Yulfiperius, Yulfiperius; Supadminingsih, Fahresa Nugraheni; Saputra, Julian (JST (Jurnal Sains dan Teknologi), 2022)
Coral reefs are marine ecosystem that provide homes at less 25% of all marine species. In the last decade, the use of Underwater Photo Transect (UPT) methods for coral reef monitoring has gained increased popularity. This study aimed to monitoring of coral reef condition at Dua Island, Tikus Island, Belanda Island, and Dapur Island. This study used Coral Point Count with Excel extensions (CPCe) software, to increase the efficiency of coral reef monitoring efforts. Photo transects were conducted by scuba diving. Coral reef community image was capture for every 1m across 50m transect line. A total of 30 random point samples was selected for each photo frame. Multiple photo frame were combineÂ  and for each point coded according to the code of each category, biota, and substrate at the random point. The results showed that the condition of the coral reefs in Bengkulu was in the fair to good category, while the condition of the coral reefs in the Seribu Islands was in the poor to fair category. The most common coral genera found in Bengkulu are Porites and Pocillopora, while in the Seribu Islands are Porites and Acropora.